2015
DOI: 10.1186/s12913-015-1255-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of electronic health records adoption on patient visit volume at an academic ophthalmology department

Abstract: BackgroundElectronic health records (EHRs) have become a mandated part of delivering health care in the United States. The purpose of this study is to report patient volume before and after the transition to EHR in an academic outpatient ophthalmology practice.MethodsReview of patient visits per half-day and number of support staff for established faculty ophthalmologists between July and October for five consecutive years beginning the year before EHR implementation.ResultsEight physicians met inclusion crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
0
13
1
Order By: Relevance
“…The decrease in clinical volume was minimal and transient; thus, the clinical outflow in the ophthalmology department was hardly affected by EHR implementation. That contrasts strikingly with previous studies reporting the opposite effect [19,20]. The ophthalmologists accepted the new EHR system, and the system utilization rate increased in relation to their satisfaction with the system.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The decrease in clinical volume was minimal and transient; thus, the clinical outflow in the ophthalmology department was hardly affected by EHR implementation. That contrasts strikingly with previous studies reporting the opposite effect [19,20]. The ophthalmologists accepted the new EHR system, and the system utilization rate increased in relation to their satisfaction with the system.…”
Section: Discussioncontrasting
confidence: 93%
“…The ophthalmologists accepted the new EHR system, and the system utilization rate increased in relation to their satisfaction with the system. Nevertheless, most ophthalmologists still have concerns regarding the potential adverse effects on productivity and efficiency in ophthalmology practice [18,19,21]. Furthermore, a recent survey found that ophthalmologists' rate of satisfaction with their EHR has decreased [17].…”
Section: Discussionmentioning
confidence: 99%
“…While EHR use is sometimes thought to lengthen clinical encounters among ophthalmologists and the field of medicine as a whole, studies examining the impact of EHR implementation on ophthalmology practices have demonstrated a mixed impact on patient volume and the time physicians spend in clinic. 5,[22][23][24][25][26][27][28] In our study, the total time that residents and fellows spent per patient encounter did not change with EHR implementation. Average time spent on a patient encounter during a paper chart-based encounter was 11.6 minutes, compared with 11.8 minutes spent on a patient encounter when using the EHR.…”
Section: Discussionmentioning
confidence: 99%
“…The many points of debate around electronic medical records have addressed important issues ranging from the use of decision support tools to improved access to information [2,5,6]. Some of the most important investigations regarding electronic medical records adoption have addressed the effects of electronic medical records on emergency department operations metrics, including throughput measures such as Length of stay (LOS) [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%